2020
DOI: 10.1093/mnras/staa1015
|View full text |Cite
|
Sign up to set email alerts
|

Identifying strong lenses with unsupervised machine learning using convolutional autoencoder

Abstract: In this paper we develop a new unsupervised machine learning technique comprising of a feature extractor, a convolutional autoencoder (CAE), and a clustering algorithm consisting of a Bayesian Gaussian mixture model (BGM). We applied this technique to visual band space-based simulated imaging data from the Euclid Space Telescope using data from the Strong Gravitational Lenses Finding Challenge. Our technique promisingly captures a variety of lensing features such as Einstein rings with different radii, distort… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 111 publications
0
68
0
Order By: Relevance
“…There are currently several types of astronomical studies that apply unsupervised machine learning techniques to images which reach reasonable results, including: galaxy morphology (Hocking et al 2018;Martin et al 2020), strong lensing identification (Cheng et al 2020), and anomaly detection (Xiong et al 2018;Margalef-Bentabol et al 2020). For example, Hocking et al (2018) and Martin et al (2020) apply a technique called Growing Neural Gas algorithm (Fritzke 1994), which is a type of Self-organising Map (SOM, Kohonen 1997), to extract features from images.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are currently several types of astronomical studies that apply unsupervised machine learning techniques to images which reach reasonable results, including: galaxy morphology (Hocking et al 2018;Martin et al 2020), strong lensing identification (Cheng et al 2020), and anomaly detection (Xiong et al 2018;Margalef-Bentabol et al 2020). For example, Hocking et al (2018) and Martin et al (2020) apply a technique called Growing Neural Gas algorithm (Fritzke 1994), which is a type of Self-organising Map (SOM, Kohonen 1997), to extract features from images.…”
Section: Introductionmentioning
confidence: 99%
“…These features are then connected with a hierarchical clustering algorithm (Hastie et al 2009). On the other hand, Cheng et al (2020) use a fundamentally different approach by using a convolutional autoencoder (Masci et al 2011), which includes an architecture of convolutional neural networks, for feature extraction. This method connects the extracted features with a Bayesian Gaussian mixture model from which a clustering analysis can be done.…”
Section: Introductionmentioning
confidence: 99%
“…Several CNN searches for new strong lens candidates have focused on ground-based imaging data, from the CFHTLS (Jacobs et al 2017), KiDS DR3 (Petrillo et al 2017) and DR4 (Petrillo et al 2019;Li et al 2020), DES Year 3 (Jacobs et al 2019b,a), or the DESI DECam Legacy survey (Huang et al 2020a). Efficient classification pipelines using deep neural networks have also been developed and tested on simulated Euclid and LSST images to prepare for these forthcoming surveys which will tremendously increase the number of detectable strong lensing systems (Lanusse et al 2018;Schaefer et al 2018;Davies et al 2019;Cheng et al 2020;Avestruz et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Autoencoders prove to be a reliable form of dimensionality reduction, which allows for unsupervised clustering algorithms to be used on data sets that would otherwise be too complex. For example, Cheng et al (2020) employ an autoencoder with convolutional layers to learn a latent representation from a data set of simulated gravitational lens imaging, which is then used to perform Bayesian Mixture Modelling to build a clustering and classification scheme for determining if a given image contains a gravitational lens. Note that there exist applications of autoencoders that embed the clustering process within the network itself.…”
Section: Autoencodersmentioning
confidence: 99%
“…However, recent work has shown that unsupervised learning methods also perform well at visually classifying astronomical objects. Cheng et al (2020) used a Convolutional Autoencoder (CAE), paired with Bayesian Gaussian Mixture Models (GMMs), to successfully construct a classifier for strong gravitational lenses. Ralph et al (2019) also exploited CAEs, combining the feature extraction capability of the autoencoder with a Self-Organised Map and k-means clustering to identify different classes of radio galaxy morphology.…”
Section: Introductionmentioning
confidence: 99%